Proceedings of the 4th International Conference on Innovations in Automation and Mechatronics Engineering (ICIAME2018) - Bhavsar, Sanket N.; Joshi, Anand Y.; Tamboli, Ketan M. (IntechOpen, 2019)
The Mechatronics Department (Accredited by National Board of Accreditation, New Delhi, India) of the G H Patel College of Engineering and Technology, Gujarat, India arranged the 4th International Conference on Innovations in Automation and Mechatronics Engineering 2018, (ICIAME 2018) on 2-3 February 2018. The papers presented during the conference were based on Automation, Optimization, Computer Aided Design and Manufacturing, Nanotechnology, Solar Energy etc and are featured in this book.